2020
DOI: 10.1051/bioconf/20202100020
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic post-effect of entomopathogenic fungi on phytophagous pests and entomophagous biocontrol agents

Abstract: Phytosanitary optimization of agricultural ecosystems under conditions of glasshouses and organic farming urgently demands guaranteed effect of plant protection. This can be achieved only through effective exploitation of a complex of biological agents, including arthropod predators and parasites, entomopathogenic fungi, nematodes and other microbes. Entomopathogenic fungi Beauveria bassiana and Lecanicillium muscarium are characterized by facultative parasitism and possess high potential to control phytophago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…However, fungal isolates reduced fecundity, fertility, and hatching of S. frugiperda eggs. This is in accordance with research by Pavlyushin (2020) that showed Lecanicillium muscarium and Beauveria bassiana were able to reduce fertility of Aphis gossypii up to the fifth generation. Results by Marcinkeviciusa et al (2019) showed that the ethyl acetate extract supernatant of Fusarium sp.…”
Section: Effect Of Entomopathogenic Fungal Isolates and Their Applica...supporting
confidence: 93%
“…However, fungal isolates reduced fecundity, fertility, and hatching of S. frugiperda eggs. This is in accordance with research by Pavlyushin (2020) that showed Lecanicillium muscarium and Beauveria bassiana were able to reduce fertility of Aphis gossypii up to the fifth generation. Results by Marcinkeviciusa et al (2019) showed that the ethyl acetate extract supernatant of Fusarium sp.…”
Section: Effect Of Entomopathogenic Fungal Isolates and Their Applica...supporting
confidence: 93%